2018
DOI: 10.4103/jmh.jmh_87_17
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy among the elderly

Abstract: Introduction:Older people are at risk for polypharmacy due to multiple chronic diseases. Considering the lack of information in this regard, the aim of this study was to investigate the state of polypharmacy among the elderly in the city of Amirkola in northern part of Iran.Materials and Methods:This descriptive/analytical cross-sectional study is a part of Amirkola Health and Aging Project that was conducted on 1616 individuals aged 60 years and over. The data about medications were gathered through interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
2
16
2
Order By: Relevance
“…In previous studies done in other study areas in Iran more head lice infection was reported in females than males (16)(17)(18). In another study by Zabihi et al, the prevalence of lice infestation in women was reported as more than men, which is consistent with this present study (19). According to significant statistical association, we found that there was a significant difference between head lice infestation and history of head lice infestation.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies done in other study areas in Iran more head lice infection was reported in females than males (16)(17)(18). In another study by Zabihi et al, the prevalence of lice infestation in women was reported as more than men, which is consistent with this present study (19). According to significant statistical association, we found that there was a significant difference between head lice infestation and history of head lice infestation.…”
Section: Discussionsupporting
confidence: 92%
“… 17 Another study estimated the polypharmacy prevalence in Iran at 23.1%. 27 The overall prevalence rate in Brazil has to be understood bearing in mind the considerable internal geographic disparities, ranging from 5% in the North to 19% in the South.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous cross-sectional studies also indicated high prevalence of polypharmacy to be 39.4% in Italy, 28 29.5% in New Zealand 29 and 32.5% in Taiwan. 30 Higher prevalence of polypharmacy among the elderly population is due to the presence of different co-morbidities because of a weaker immune system that leads to possible drug-drug interactions and inappropriate use of medications. Pharmacists play a huge role in reviewing the medications of the patients, and regular support for elderly patients infected with RTIs prove beneficial in improving their quality of life.…”
Section: Discussionmentioning
confidence: 99%